Empowerment of women : promise and performance - Sachchidananda, 1926-; Mandal, B. B., 1942-; Shri Brajkishore Memorial Institute, Patna (Patna : Shri Braj Kishore Memorial Institute, 1998)
Contributed articles presented at a seminar moderated by the Shri Brajkishore Memorial Institute, Patna.
Keywords: Women in development -- India -- Bihar -- Congresses